2013
DOI: 10.1371/journal.pone.0077913
|View full text |Cite
|
Sign up to set email alerts
|

Serum Copeptin and Cortisol Do Not Accurately Predict Sickle Cell Anaemia Vaso-Occlusive Crisis as C-Reactive Protein

Abstract: ObjectiveThis study assessed the diagnostic performance and prognostic properties of C-reactive protein (CRP), copeptin and cortisol in individuals with sickle cell anaemia (SCA).DesignProspective case-control studyMethodsSixty consecutive SCA subjects (18–40 years) comprising 30 subjects in the steady state and 30 subjects in vaso-occlusive crisis (VOC) were recruited into this study. Thirty (30) apparently healthy individuals with HbAA genotype served as controls. ELISA was used for the determination of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The interaction between SCA complications such as VOC and disturbed metabolic homeostasis in individuals with SCA has been reported 1419. In this study, TC and LDL decreased progressively from control-to-SSCA-to-VOC.…”
Section: Discussionsupporting
confidence: 52%
“…The interaction between SCA complications such as VOC and disturbed metabolic homeostasis in individuals with SCA has been reported 1419. In this study, TC and LDL decreased progressively from control-to-SSCA-to-VOC.…”
Section: Discussionsupporting
confidence: 52%
“…ACS has a multifactorial etiology, including a variety of inciting events that trigger deoxygenation of HbS, leading to its polymerization and to red blood cell sickling with subsequent vaso-occlusion, ischemia, and endothelial dysfunction (9,10). Heightened proinflammatory cytokine production has been reported in individuals with SCA during VOC (7). Elevated levels of CRP, a general marker of inflammation, have previously been reported in ACS patients with SCD (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have reported a strong association between increased CRP levels and VOC. The elevated CRP in SCD may be in response to endothelial damage due to the blockage of the vascular endothelium by sickled erythrocytes (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory investigations have linked mental problems with excessive stress. High cortisol levels reflect a higher degree of stress, but are dependent on the integrity of the HPA-axis [12]. Also, elevated plasma levels of arginine vasopressin (AVP) which is another stress hormone produced through HPA axis activity has been reported in schizophrenic patients [13].…”
Section: Introductionmentioning
confidence: 99%